Toward whole tissue imaging of axolotl regeneration. Issue 6 (31st December 2020) - Masselink, Wouter; Tanaka, Elly M.
Abstract: The axolotl is a highly regenerative organism and has been studied in laboratories for over 150 years. Despite a long‐standing fascination with regeneration in general and axolotl specifically, we are still scratching the surface trying to visualize and understand the complex cellular behavior that underlies axolotl regeneration. In this review, we will discuss the progress that has been made in visualizing these processes focusing on four major aspects: cell labeling approaches, the removal of pigmentation, reductionist approaches to perform live cell imaging, and finally recent developments applying tissue clearing strategies to visualize the processes that underly regeneration. We also provide several suggestions that the community could consider exploring, notably the generation of novel alleles that further reduce pigmentation as well as improvements in tissue clearing strategies. Key Findings: Historical perspective on axolotl imaging and lineage tracing Description of tissue clearing approaches Refractive index matching strategies Strategies to further reduce pigmentation in axolotl